Pengujian Panel Surya Dinamik Dan Statik Dengan Melakukan Perbandingan Daya Output - Wahyu Fajaryanto; Adhy Prayitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Some consideration in generating electrical energy is to produce big enough energy, economical cost andnot have negative impact to environment. In this test has been made mechanical system that can move solarpanel to the sun and Know the comparison of solar panel power output between solar panels Dynamics andstatic solar panels. The dynamic solar panel output power and static solar panels are both increasing in timefollowing the position of the sun. Optimum power of solar panels occur at midmorning until the beginning of thesun slip.From the test results found that the highest level of voltage levels are at 11:30 to 12:30. This is becausethe sun is just above the daily sunshineKeywords : solar panel, solar panel dynamic,solar panel static